Religious Stereotypes in YouTube Educational Videos to Address Controversy and Manipulation in Elementary School Classroom Environments - Rini, Ambar; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2024)
The phenomenon of religious stereotypes in educational videos on YouTube has become a worrying issue, especially in the context of early childhood education. With the increasing use of this platform as a learning tool, it is important to explore the negative impacts that may be caused by content that presents biased information. These stereotypes have the potential to influence students' perceptions of religion and create social tensions within the elementary school classroom environment. This study aims to examine the impact of religious stereotypes in educational videos and their implications for students' social interactions in the classroom. In this study, we used a qualitative approach involving video content analysis and in-depth interviews with teachers and students. The results showed that video content containing religious stereotypes contributed to misunderstandings and created tensions among students. Many students reported that they were influenced by the way religion was presented in the videos, which often did not reflect the reality of actual religious practices. These findings emphasize the need for a critical review of educational media content to prevent potential manipulation of information and controversies that can be detrimental to the learning process. In conclusion, this study recommends the development of comprehensive guidelines for evaluating and filtering educational content on YouTube, to ensure more inclusive and accurate representation of religion. This effort is important to build a positive learning environment and support the values of tolerance and interfaith understanding among students